Understanding the dynamics of online learning communities; experiences from three university courses - Chuang, Victoria Jae; Ceballos, Alejandro; Bundgaard, Helle; Furu, Peter; Bregnhøj, Henrik; Harker-Schuch, Inez; Henriksen, Christian Bugge (Tidsskriftet Læring og Medier (LOM), 2016)
Online learning communities are a foundational element of online and blended learning. Many learning activities in online and blended learning courses require students to collaborate and work together with their peers. In order for these learning activities to be successful it is important that participants are engaged socially and emotionally in their online interaction to create a sense of community and cohesion, corresponding to what constitutes Social Presence in the Community of Inquiry Framework model. As teachers, we therefore focus on creating learning designs that facilitate the development of online learning communities. In this article, we examine the development of online learning communities in online discussion forums. We map a selection of discussion threads from three university-level courses using the NodeXL software, and discuss the implications of e.g. structure, facilitation and group size on the online learning community that emerges. We find that the framework for participation in discussions (e.g. level of guidance and role of facilitators) affects the degree of connectivity within the online learning community and the prevalence of “social” posting, which has implications for strengthening the community and student-to-student support throughout the course.